The Effect of Post-Learning Wakeful Rest on the Retention of Second Language Learning Material over the Long Term - Martini, Markus; Riedlsperger, Benjamin; Maran, Thomas; Sachse, Pierre (Current psychology (New Brunswick, N.J.), 2020)
Evidence exists that a brief period of wakeful rest after learning supports memory retention, while interference after learning weakens memory retention. We tested this so-called resting effect for second language learning material. In two counterbalanced within-subject designs, participants were involved in two identical successive learning phases. In each phase, they learned one of two second language stories, immediately followed by a recall phase in the first language. The critical manipulation took place after the immediate recall. Here, participants either rested or worked on a distractor task for 8 min. In Experiment 1, participants worked on a spot-the-difference task (visual distractor condition), and in Experiment 2, they read a New York Times article (verbal distractor condition). After 7 days, all participants were again invited to a second experimental session, where a surprise free recall test took place. Our results showed that second language story retention over a period of 7 days was not supported by a brief period of wakeful rest following learning and recall, independent of the distractor condition. Our findings contribute to an important characterization of the wakeful resting effect in younger adults, which is discussed in the light of existing studies.